Enhancing Risk Detection Among Homeless Youth: A Randomized Clinical Trial of a Promising Pilot Intervention. Issue 19 (October 2018) - Bender, Kimberly A.; DePrince, Anne; Begun, Stephanie; Hathaway, Jessica; Haffejee, Badiah; Schau, Nicholas
Homeless youth frequently experience victimization, and youth with histories of trauma often fail to detect danger risks, making them vulnerable to subsequent victimization. The current study describes a pilot test of a skills-based intervention designed to improve risk detection among homeless youth through focusing attention to internal, interpersonal, and environmental cues. Youth aged 18 to 21 years ( N = 74) were recruited from a shelter and randomly assigned to receive usual case management services or usual services plus a 3-day manualized risk detection intervention. Pretest and posttest interviews assessed youths' risk detection abilities through vignettes describing risky situations and asking youth to identify risk cues present. Separate 2 (intervention vs. control) × 2 (pretest vs. posttest) mixed ANOVAs found significant interaction effects, as intervention youth significantly improved in overall risk detection compared with control youth. Post hoc subgroup analyses found the intervention had a greater effect for youth without previous experiences of indirect victimization than those with previous indirect victimization experiences.